Antithrombotic Management for Patients with Atrial Fibrillation Undergoing Percutaneous Coronary Intervention - A. V. Panov (Рациональная фармакотерапия в кардиологии, 2021)
Comprehensive protection of a patient with atrial fibrillation (AF) should not only reduce the risk of stroke and systemic embolism, but also reduce the risk coronary events and ensure high adherence to treatment. In accordance with consensus document issued by the European Heart Rhythm Association, European Society of Cardiology, European Association of Percutaneous Cardiovascular Interventions, as well as with other recent Russian Society of Cardiology Guidelines, the management of antithrombotic therapy of patients with AF undergoing percutaneous coronary intervention (PCI) requires that multiple and interconnected issues. The review article addresses questions about duration of initial triple antithrombotic therapy (TAT), selection of P2Y12 inhibitor, choice of oral anticoagulant to be combined with antiplatelet therapy, intensity of oral anticoagulation throughout combination therapy, and choice of oral anticoagulant for indefinite therapy. In general, it is recommended to refuse the routine use of TAT for most patients. Accordingly, for patients who need both anticoagulant and antiplatelet therapy, it is strongly recommended that the default strategy after recent PCI is a double antithrombotic therapy consisting of an anticoagulant and one antiplatelet, preferably from the group of P2Y12 inhibitors. When conducting combined antithrombotic therapy, preference should be given to clopidogrel compared to other, more powerful P2Y12 inhibitors and direct oral anticoagulant (DOAC) instead of vitamin K antagonists. The primary choice of DOAC in patients with AF who have undergone PCI should be carried out taking into account such factors as individual risk of stroke and bleeding, adherence to treatment, concomitant diseases, pharmacological characteristics and evidence base of a specific DOAC, taking other medications, etc. The pharmacokinetic features of rivaroxaban, which create the possibility of its single administration, the evidence base for reducing coronary risks in various variants of the course of coronary heart disease, determines the special positions of the drug for the comprehensive protection of patients with AF after PCI.